Performance Improvement Strategy With Malcolm Baldrige Method Integration and SWOT Analysis (Case Study at UD. Syaiful Plastik) - Mohammad Aji Prasetyo; Hana Catur Wahyuni (Procedia of Engineering and Life Science, 2021)
There are problems that faced at UD. Syaiful Plastik including in the sector of leadership, measurement management, and company product output. This results in the quality and quantity of the company's products not being able to fulfill consumer expectations. To follow up on this problem, the Malcolm Baldrige method is used to analyze the company's performance with seven categories of assessment and SWOT analysis to determine the factorc that affect the company's performance, by assessing internal factors (strenghts and weaknesses), external factors (opportunities and threats). From the measurement results, Malcolm Baldrige's total score is 474 points with an overall percentage of 47% from a maximum score of 1000. This value is at the average level including the early improvement category (point scale 376-475). The results of the internal evaluation contained 8 attributes of strength elements and 4 attributes of weakness elements. The results of the external evaluation contained 5 opportunity attributes and 5 threat attributes. Mapping the IFE-EFE matrix followed by a SWOT analysis resulted in 4 alternative strategies that can be done to build progress and a more competitive company advantage.